Dual liquid crystal alignment configuration based on nanoparticle-doped polymer films - Fuh, Andy Ying-Guey; Huang, Chen-Yu; Liu, Cheng-Kai; Chen, Yuan-Di; Cheng, Ko-Ting (Optics express, 2011)
This paper proposes an approach for producing dual liquid crystal (LC) alignment configuration based on nanoparticle-doped polymer films. Experimental results indicate that illuminating a nanoparticle-doped pre-polymer film, coated onto a substrate with a homogeneous alignment layer, with unpolarized UV light through a photomask causes the polymerization of pre-polymer, ultimately generating homogeneous and vertical alignment layers in unpolymerized and polymerized regions, respectively. The dual LC alignment configuration of the homogeneous (vertical) and hybrid alignments can be achieved by combining the treated substrate with another substrate that has a homogeneous (vertical) alignment layer. Additionally, the applications of the dual LC alignment layer in phase gratings and transflective LC displays are demonstrated.